PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION TERHADAP HASIL BELAJAR BAHASA INDONESIA PADA MATERI TEKS EKSPLANASI KELAS VI SDN - Samuel Sianturi; Edizal Hatmi; Nurmayani; Winara; Masta Marselina Sembiring (STKIP Subang, 2026)
This study aims to determine whether there is an effect of using the Team Assisted Individualization cooperative learning model on the learning outcomes of Indonesian Language in the Explanatory Text material for sixth grade students at SDN. This research was conducted at SD NEGERI 104202 Bandar Setia, located on Jln. Terusan, Dusun V Bandar Setia, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province, in the even semester of the 2025/2026 academic year. This study used a quasi-experimental design and a nonequivalent control group design. The sample size was 40 students, determined using total sampling. The results of the study were obtained from the Independent Sample T Test with a significance value of 0.000 < 0.05. The N-Gain test results obtained an N-Gain Score of 0.5500, and the N-Gain test score in this study was classified as moderate. Meanwhile, the N-Gain percent score was 54.9991, which according to the N-Gain test classification, means that this study was quite effective. Based on these results, it can be concluded that the use of the Team Assisted Individualization cooperative learning model had an effect and was quite effective on the Indonesian language learning outcomes for the Explanatory Text material in grade VI of SD Negeri 104202 Bandar Setia.